2020
DOI: 10.22460/project.v3i1.p120-126
|View full text |Cite
|
Sign up to set email alerts
|

Project-Based Learning Approach to Improve Students’ Writing Skill

Abstract: This research was held during the internship at SMPK BPK PENABUR Cimahi by taking the material taught in English lesson for 8th grade students at first semester. The objective of this research is to find out the improvement of writing imperative sentence using Project-Based Learning approach. The use of Project Based Learning approach suited with the Kurikulum 2013, which has been used by this school since 2013. The method used Classroom Action Research (CAR), which held on two cycles for seven meeting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
(4 reference statements)
0
3
0
Order By: Relevance
“… * To avoid the inclusion of literature that did not provide group size numbers from influencing the study results, only literature that did provide data was included in the analysis here. Other literature included in the meta-analysis ( Beier et al, 2019 ; Castro-Vargas et al, 2020 ; Chung, 2021 ; Ergül and Kargın, 2014 ; Hugerat, 2016 ; Hung et al, 2012 ; Lazić et al, 2021 ; Lin and Lu, 2018 ; Mark, 2022 ; Ozdamli and Turan, 2017 ; Ruiz-Rosa et al (2013 ; Wang et al, 2016 ; Wurdinger and Qureshi, 2015 ; Zulaeha et al, 2020 .). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… * To avoid the inclusion of literature that did not provide group size numbers from influencing the study results, only literature that did provide data was included in the analysis here. Other literature included in the meta-analysis ( Beier et al, 2019 ; Castro-Vargas et al, 2020 ; Chung, 2021 ; Ergül and Kargın, 2014 ; Hugerat, 2016 ; Hung et al, 2012 ; Lazić et al, 2021 ; Lin and Lu, 2018 ; Mark, 2022 ; Ozdamli and Turan, 2017 ; Ruiz-Rosa et al (2013 ; Wang et al, 2016 ; Wurdinger and Qureshi, 2015 ; Zulaeha et al, 2020 .). …”
Section: Resultsmentioning
confidence: 99%
“…Other literature included in the meta-analysis ( Beier et al, 2019 ; Castro-Vargas et al, 2020 ; Chung, 2021 ; Ergül and Kargın, 2014 ; Hugerat, 2016 ; Hung et al, 2012 ; Lazić et al, 2021 ; Lin and Lu, 2018 ; Mark, 2022 ; Ozdamli and Turan, 2017 ; Ruiz-Rosa et al (2013 ; Wang et al, 2016 ; Wurdinger and Qureshi, 2015 ; Zulaeha et al, 2020 .).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A research conducted (Nikmah et al, 2022) by hows the outcome essentially demonstrates that interactive Powerpoint is adequate for usage as a teaching and learning tool to teach reading in junior highschool, and also the research conducted by (Rahayu et al, 2023) shows positive results which is the interactive Powerpoint to teach English is suitable for use in the learning process. It means interactive learning media might be applied in class.…”
Section: Introductionmentioning
confidence: 92%
“…Previous research on project-based learning approach to improve students' writing skills by (Zulaeha & Marpaung, 2020) shows that project based learning improve individual activities and participation in the group. Its indicated that the Project Based Learning approach was the right approach to apply in learn writing.…”
Section: Introductionmentioning
confidence: 99%